Quantification of bone marrow edema by MRI of the sacroiliac joints in patients diagnosed with axial spondyloarthritis: results from the ESPeranza cohort. (3rd September 2022) - Almodovar, R; Bueno, A; Garcia Monco, C; De Miguel, E; Tornero, C; Moreno, M; Gratacos, J; Zarco, P; Mazzucchelli, R
Abstract : Objective: To evaluate whether the quantification of bone marrow edema (BMO) of the sacroiliac (SI) joints by magnetic resonance imaging (MRI) improves capacity for axial spondyloarthritis (axSpA) classification in comparison with the assessment of sacroiliitis by Assessment of SpondyloArthritis international Society (ASAS) classification criteria. Method: This prospective study from the ESPeranza cohort involved 66 subjects with an available MRI of the SI joints at baseline. This subgroup includes patients with axSpA (n = 28), peripheral spondyloarthritis (n = 10), and other diagnoses that were not spondyloarthritis (n = 28). Measures of diagnostic usefulness [area under the curve (AUC), sensitivity, specificity, Youden's J statistic, positive and negative likelihood ratios (LR+ and LR−)] were calculated for MRI of the SI joints according to ASAS criteria and for MRI quantified by means of SCAISS (Spanish tool for semi-automatic quantification of sacroiliac inflammation by MRI in spondyloarthritis). This analysis was stratified in patients who were human leucocyte antigen (HLA)-B27 positive and negative. Results: The AUC value with BMO quantification was 0.919 [95% confidence interval (CI) 0.799–1] for HLA-B27-positive patients and 0.884 (95% CI 0.764–1) for HLA-B27-negative patients. A SCAISS cut-off point of 80 units obtained a specificity of 94.4% and LR+ 7.5, while assessment by ASAS criteria showed a specificity value of 90% and LR+ 6.4. Conclusion: For patients with suspected axSpA, quantification of BMO improves the predictive capacity of MRI of the SI joints, for both HLA-B27-positive and HLA-B27-negative patients. Axial spondyloarthritis (axSpA) has a dramatic impact on physical function and quality of life (1 ). Despite its significant impact, patients with axSpA are normally diagnosed several years after presenting symptoms (2 ). In this respect, magnetic resonance imaging (MRI) of the sacroiliac (SI) joints has gained significance over the past decade, particularly in the early stages of the disease. Nowadays, imaging tests and human leucocyte antigen (HLA)-B27 testing are among the most important diagnostic procedures for patients with suspected axSpA.